Leucaena + maize alley cropping in Malawi: Part 1: Effects of N, P, and leaf application on maize yields and soil properties - Jones, R.B.; Wendt, W.; Bunderson, W.T.; Itimu, O.A. (Springer, 1996)
Yields under alley cropping might be improved if the most limiting nutrients not adequately supplied or cycled by the leaves could be added as an inorganic fertilizer supplement. Three historic leaf management strategies had been in effect for 3 years in a Leucaena leucocephala alley cropping trial on the Lilongwe Plain of central Malawi: I) leaves returned; 2) leaves removed; and 3) leaves removed, with 100 kg inorganic N ha-I added. An initial soil analysis showed P status to be suboptimal under all strategies. A confounded 34 factorial experiment was conducted with the following treatments: leaf management strategy (as above), N fertilizer rate (0, 30, and 60 kg N ha-I ), P fertilizer rate (0, 18, and 35 kg P ha- I ), and maize population (14,800, 29,600, and 44,400 plants ha-I ). Both Nand P were yield limiting, and interacted positively to improve yields. The addition of 30 kg Nand 18 kg P ha-1 improved yields similarly under all leaf management strategies by an average of 2440 kg ha-1. Increasing the rates to 60 kg Nand 35 kg P ha-1 improved yields an additional 1990 kg ha-1 in the 'leaves returned' and 'leaves removed + N' strategies, but did not improve yields under the 'leaves removed' strategy. Lower yields were related to lack of P response at the highest P rate in this treatment, which may have induced Zn deficiency. Plots receiving leaves had higher organic C, total N, pH, exchangeable Ca, Mg, K, and S, and lower C/N ratios in the 0-15 cm soil layer than did plots where leaves had been removed. Leaf removal with N addition was similar to leaf removal alone for all soil factors measured except for organic C and total N, which were higher where N had been added. The results show that Nand P were the primary yield-limiting nutrients. Historic N application maintained the soil's ability to respond to Nand P on par with leaf additions.